The Increasing Prevalence of Obesity in Residents of U.S. Nursing Homes: 2005–2015. (23rd January 2019) - Zhang, Ning; Field, Terry; Mazor, Kathleen M; Zhou, Yanhua; Lapane, Kate L; Gurwitz, Jerry H
Abstract: Background: Obesity prevalence has been increasing over decades among the U.S. population. This study analyzed trends in obesity prevalence among long-stay nursing home residents from 2005 to 2015. Methods: Data came from the Minimum Data Sets (2005–2015). The study population was limited to long-stay residents (ie, those residing in a nursing home ≥100 days in a year). Residents were stratified into body mass index (BMI)-based groups: underweight (BMI < 18.5), normal weight (18.5 ≤ BMI < 25), overweight (25 ≤ BMI < 30), and obese (BMI ≥ 30); residents with obesity were further categorized as having Class I (30 ≤ BMI < 35), Class II (35 ≤ BMI < 40), or Class III (BMI ≥ 40) obesity. Minimum Data Sets assessments for 2015 were used to compare clinical and functional characteristics across these groups. Results: Obesity prevalence increased from 22.4% in 2005 to 28.0% in 2015. The prevalence of Class III obesity increased from 4.0% to 6.2%. The prevalence of underweight, normal weight, and overweight decreased from 8.5% to 7.2%, from 40.3% to 37.1%, and from 28.9% to 27.8%, respectively. In 2015, compared with residents with normal weight, residents with obesity were younger, were less likely to be cognitively impaired, had high levels of mobility impairment, and were more likely to have important medical morbidities. Conclusions and Relevance: There was a steady upward trend in obesity prevalence among nursing home residents for 2005–2015. Medical and functional characteristics of these residents may affect the type and level of care required, putting financial and staffing pressure on nursing homes.